2007 SBMO/IEEE MTT-S International Microwave and Optoelectronics Conference 2007
DOI: 10.1109/imoc.2007.4404320
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of integrated electro-absorption modulated laser structures for 100 Gbit/s ethernet using electromagnetic simulation

Abstract: Abstract-In this paper three options for very-high bit rate integrated electro-absorption modulated laser (EML) structures are investigated using electromagnetic simulation. A physics based distributed equivalent circuit model taking the slowwave propagation characteristics of the modulation signal into account is proposed for the electro-absorption modulator (EAM) electrode arrangement. This model makes it possible to apply an EM/circuit co-simulation approach to estimate the electrical to optical transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…It should be observed that both the amplitude and the phase are accurately captured in the EM simulations as compared to measurements up to 65 GHz. This verifies the EML intrinsic circuit model developed in [8]. Given this EML circuit model it is possible to investigate the EML embedding circuitry.…”
Section: Ieee Mtt-s International Microwave Workhop Series Onsupporting
confidence: 71%
See 2 more Smart Citations
“…It should be observed that both the amplitude and the phase are accurately captured in the EM simulations as compared to measurements up to 65 GHz. This verifies the EML intrinsic circuit model developed in [8]. Given this EML circuit model it is possible to investigate the EML embedding circuitry.…”
Section: Ieee Mtt-s International Microwave Workhop Series Onsupporting
confidence: 71%
“…Instead a lumped smallsignal equivalent circuit model for the MQW stack in the EAM and the laser junction parts are included into the HFSS EM simulation. This can be accomplished by using lumped RCL-boundary conditions available in the Ansoft HFSS simulator [8]. For the EAM junction typical values for the junction capacitance Cs and dynamic photocurrentresistance Rph are substituted into the HFSS simulation domain, while a single capacitor Claser is substituted for the laser MQW in a similar manner.…”
Section: Ieee Mtt-s International Microwave Workhop Series Onmentioning
confidence: 99%
See 1 more Smart Citation